2018
DOI: 10.11114/jets.v6i12.3661
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Teacher Candidates’ Self-Efficacy, Motivation and Affection Levels for Children

Abstract: The purpose of this research is to reveal the levels of affection for children, teaching motivations and self-efficacy beliefs of the teacher candidates studying in special education, pre-school and primary school teaching departments based on their gender, classroom and academic branches to showcase the correlations between the levels of the teachers" affection for children, their self-efficacy beliefs and teaching motivations. The study group was determined with the criterion sampling method. 368 teacher can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 28 publications
(46 reference statements)
0
4
0
Order By: Relevance
“…In a study where there were pre-service primary school teachers enrolled in Ethiopia's Wollega University, it was concluded that a moderate positive attitude was exhibited towards the profession of teaching (Merdassa, 2012). When the studies carried out related to this topic are examined, it is seen that pre-service primary school teachers have positive and high teaching motivations (Büyükses, 2010;Gün & Turabik, 2019;Lam, 2012;Wanga & Liub, 2008;Yildiz Demirtaş, 2018). When the studies are analyzed, whereas the participants' teaching profession attitudes, the other dimension of the study, are examined, Ayık & Ataş (2014) showed in their study that preservice teachers had a positive attitude towards their professions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study where there were pre-service primary school teachers enrolled in Ethiopia's Wollega University, it was concluded that a moderate positive attitude was exhibited towards the profession of teaching (Merdassa, 2012). When the studies carried out related to this topic are examined, it is seen that pre-service primary school teachers have positive and high teaching motivations (Büyükses, 2010;Gün & Turabik, 2019;Lam, 2012;Wanga & Liub, 2008;Yildiz Demirtaş, 2018). When the studies are analyzed, whereas the participants' teaching profession attitudes, the other dimension of the study, are examined, Ayık & Ataş (2014) showed in their study that preservice teachers had a positive attitude towards their professions.…”
Section: Discussionmentioning
confidence: 99%
“…When the literature was reviewed, there were studies in which pre-service primary school teachers' teaching motivations (Afzal, Ali, & Khan, 2010;Ayık, Akdemir, & Seçer, 2015;Endler, Rey, & Butz, 2012;Gün & Turabik, 2019;Kauffman, Yılmaz Soylu, & Duke, 2011;Lam, 2012;Sinclair, Dowson, & Mcinerney, 2006;Ömür & Nartgün, 2013;Wanga & Liub, 2008;Watters & Ginns, 2000;Yenilmez, Balbağ, & Turğut, 2018;Yıldız, 2010;Yildiz Demirtaş, 2018) and teaching profession attitudes (Altunkeser & Ünal, 2015;Baykara-Pehlivan, 2004;Baykara-Pehlivan, 2008;Çiğdem, 2010;Çiğdem & Memiş, 2011;Dağ, 2010;Doğan, 2013;Erdem & Anılan, 2000;Hoşgörür, Kılıç, & Dündar, 2002;Jahan, 2017;İlter & Köksalan, 2011;İpek & Camadan, 2012;İpek, Kahveci & Camadan, 2015;Kahramanoğlu, et. al., 2018;Kahyaoğlu & Yangın, 2007;Kaya, 2017;Kılıç & Bektaş, 2008;Sarikaya, Töman, & Öztürk, 2018;Serin, Güneş, & Değirmenci, 2015;Soibamcha, 2016;Sönmez, Işık, & Sulak, 2017;Şen, 2006;Şenol & Akdağ, 2018;Tümkaya, 2011;Özkan, 2017;…”
Section: Introductionmentioning
confidence: 99%
“…Individuals with high levels of self-efficacy are highly motivated, and have individual achievements ( Engin, 2020 ). Demirtas (2018) argued that teachers with high levels of self-efficacy strongly rely on their capability to accomplish in challenging situations, make the demanding decision for their success, and cope with disappointing experiences. Heuven et al (2006) stated that efficacious instructors are motivated to employ resources in educational contexts to manage arduous activities appropriately.…”
Section: Review Of Literaturementioning
confidence: 99%
“…They can also train sports elites to support national champions. Achieving these goals requires the skills, motivation and self-efficacy of the teacher in facing the various challenges of the career (1). Teachers' self-efficacy is one of the most important issues for teacher empowerment.…”
Section: Introductionmentioning
confidence: 99%